2015
DOI: 10.3892/etm.2015.2174
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of probiotics as adjuvant agents for Helicobacter pylori infection: A meta-analysis

Abstract: The aim of the present study was to determine whether probiotics could help to improve the eradication rates and reduce the side effects associated with anti-Helicobacter pylori treatment, and to investigate the optimal time and duration of probiotic administration during the treatment, thus providing clinical practice guidelines for eradication success worldwide. By searching Pubmed, Embase, the Cochrane Central Register of Controlled Trials and the Science Citation Index, all the randomized controlled trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 59 publications
(116 reference statements)
5
50
0
22
Order By: Relevance
“…Although some studies have reported that probiotics alone have limited efficacy [125,126] , they can be useful when used as a supplemental drug. In a study by Lv et al [127] , the cure rates in the probiotic supplementation group were superior to those in the group that did not receive probiotics (RR, 1.12; 95%CI: 1.06-1.19), and probiotics reduced the risk of H. pylori therapy related side effects (RR, 0.60; 95%CI: 0.40-0.91). In another meta-analysis, the pooled odd ratios (ORs) for the eradication rate were higher in the probiotic group than the control group (OR = 1.67; 95%CI: 1.38-2.02) by ITT, and adverse effects were lower in the probiotic group (OR = 0.49, 95%CI: 0.26-0.94) [128] .…”
Section: Probiotics As Another Approach To Improve Eradication Ratesmentioning
confidence: 99%
“…Although some studies have reported that probiotics alone have limited efficacy [125,126] , they can be useful when used as a supplemental drug. In a study by Lv et al [127] , the cure rates in the probiotic supplementation group were superior to those in the group that did not receive probiotics (RR, 1.12; 95%CI: 1.06-1.19), and probiotics reduced the risk of H. pylori therapy related side effects (RR, 0.60; 95%CI: 0.40-0.91). In another meta-analysis, the pooled odd ratios (ORs) for the eradication rate were higher in the probiotic group than the control group (OR = 1.67; 95%CI: 1.38-2.02) by ITT, and adverse effects were lower in the probiotic group (OR = 0.49, 95%CI: 0.26-0.94) [128] .…”
Section: Probiotics As Another Approach To Improve Eradication Ratesmentioning
confidence: 99%
“…Owing to the growing need for newer alternative eradication regimens or adjuvant treatments, the addition of probiotics (administration of live microbial species) has been considered likely to offer beneficial health effects (15) and thus has attracted substantial interest with respect to H. pylori eradication therapy (16)(17)(18)(19). On the basis of the demonstration of anti-H. pylori activity of probiotics such as Lactobacillus, Saccharomyces boulardii, and Bifidobacterium, in in vitro and experimental models of H. pylori infection (19), probiotics have been suggested to improve H. pylori eradication and reduce side effects during therapy (17,20,21).…”
mentioning
confidence: 99%
“…On the basis of the demonstration of anti-H. pylori activity of probiotics such as Lactobacillus, Saccharomyces boulardii, and Bifidobacterium, in in vitro and experimental models of H. pylori infection (19), probiotics have been suggested to improve H. pylori eradication and reduce side effects during therapy (17,20,21). However, findings from clinical studies on the use of probiotics as an adjuvant therapy to H. pylori infection have been inconsistent, with the demonstration of reduced side effects of antibiotics and improved eradication rates in some studies (16,(22)(23)(24)(25)(26)(27)(28)(29)(30), while no significant effects of adjuvant probiotics on eradication rates (22,(31)(32)(33)(34)(35)(36) or side effects (26,27,30,31,32,33,(35)(36)(37) have been reported in other studies.…”
mentioning
confidence: 99%
“…Using probiotics in the treatment of H.pylori can reduce the side effects and using probiotics more than two week and including lactobacillus significantly enhanced the efficacy of the eradication 44 . Probiotics have shown their positive effects via maintaining gastric mucosal barrier and acidity and providing protection against the harmful effects of H.pylori infection.…”
Section: Relationships With Other Diseases Of Hpylori Infectionmentioning
confidence: 99%
“…In addition, probiotics provide a better compliance the treatment as a result of reduced side effects to the intestines 45 . Mechanisms explaining the effects of probiotics on H.pylori are described as; competing against H.pylori on the gastric mucosal epithelium, providing the production of anti H.pylori substances such as acetic acid, propionic acid and butyric acid, supporting the regulation of immune functions and immunoglobulin-A secretion to improve mucosal defensive ability and strengthening the bonds between epithelial cells 44 . Although probiotics have beneficial effects on H.pylori, the impacts on H.pylori eradication are still controversial due to insufficient data on the effctive certain strain and dosage of probiotics 46 .…”
Section: Relationships With Other Diseases Of Hpylori Infectionmentioning
confidence: 99%